2007
DOI: 10.1086/520610
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Vacuolar Protein Sorting Pathway in Ebola Virus Release Independent of TSG101 Interaction

Abstract: Budding of Ebola virus (EBOV) particles from the plasma membrane of infected cells requires viral and host proteins. EBOV virus matrix protein VP40 recruits TSG101, an ESCRT-1 (host cell endosomal sorting complex required for transport-1) complex protein in the vacuolar protein sorting (vps) pathway, to the plasma membrane during budding. Involvement of other vps proteins in EBOV budding has not been established. Therefore, we used VP40 deletion analysis, virus-like particle-release assays, and confocal micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 19 publications
4
52
1
Order By: Relevance
“…To examine the ability of BST-2 to inhibit budding of such VLPs, 293T cells, in which expression levels of endogenous BST-2 are minimal (49), were transiently transfected with HA-tagged arenaviral Z, filoviral VP40, or NiV M, together with FLAG-tagged human or murine BST-2. Transfection of an empty expression vector was used as a negative control, and transfection of a vector expressing an enzymatically inactive VPS4A mutant (E228Q) (21) was used as positive control since this cellular AAA-type ATPase has previously been demonstrated to be involved in budding of different enveloped viruses (21,34,37,58,62). Release of VLPs and expression levels of the different matrix proteins in cell lysates were evaluated by Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the ability of BST-2 to inhibit budding of such VLPs, 293T cells, in which expression levels of endogenous BST-2 are minimal (49), were transiently transfected with HA-tagged arenaviral Z, filoviral VP40, or NiV M, together with FLAG-tagged human or murine BST-2. Transfection of an empty expression vector was used as a negative control, and transfection of a vector expressing an enzymatically inactive VPS4A mutant (E228Q) (21) was used as positive control since this cellular AAA-type ATPase has previously been demonstrated to be involved in budding of different enveloped viruses (21,34,37,58,62). Release of VLPs and expression levels of the different matrix proteins in cell lysates were evaluated by Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding human or murine FLAG-BST-2, HIV-1 Vpu-V5, ZEBOV (isolate Mayinga) NP-V5, VP35-V5, VP30-V5, V5-VP24, HA-VP40, GP 1,2 , GP 1,2 -V5 lacking the mucin-like domain (GP 1,2 ⌬MLD-V5), sGP-V5, ssGP-V5, and ⌬-peptide-V5; MARV (isolate Musoke) HA-VP40, MACV (strain Carvallo) Z-HA, NP-V5, and L; LASV (strain Josiah) SSP-V5, Z-HA, and NP-V5; and NiV M-HA were commercially synthesized (Geneart AG or Blue Heron Biotechnology). Plasmid encoding EGFP-VPS4A E228Q was previously described (58). Filoviral HA-VP40, arenaviral Z-HA, and NiV M-HA were cloned into the pCAGGS expression plasmid (54).…”
Section: Methodsmentioning
confidence: 99%
“…We used a recombinant, GFP-expressing strain of EBOV to conduct a high-throughput screen of nonpeptidic small-mole- We have shown previously that EBOV utilizes the host vacuolar protein sorting (vps) machinery in general for efficient budding (17,18). A component of the vps system, TSG101, has been shown to be involved with both EBOV (15, 17)-and MARV (22)-derived VP40 to mediate viral budding and release.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that ebola VP40 can partially redirect the ESCRT-1 proteins Tsg101, VPS4, VPS28, and VPS37B to the cell surface (41,42). Importantly, deletion mutants or point mutants of Tsg101 or VPS4 can act in a dominant-negative manner and partially inhibit VP40-dependent VLP release (38,40,42). Work utilizing a mouse model suggests that targeting the vacuolar protein sorting pathway may be an effective therapeutic strategy against filovirus infections.…”
Section: Filovirion-associated Host Proteinsmentioning
confidence: 99%